Enhancing 7th-Grade Students’ Short Story Writing through Intercultural Learning and Visual Media - Milawati, Milawati; Mayang, Mayang; Rohmah, Dewi Wardah Mazidatur (Dinamika Ilmu, 2025)
Writing short stories in English has been one of the difficult challenges at MTs Tarbiatul Islamiah. This research aims to improve short story writing skills in English by using visual media to enhance students' abilities to write short stories in English. This study employs a quantitative research method with a quasi-experimental design of the Non-equivalent Control Group type. In this study, there are two groups that are not randomly selected. Both groups were given a pretest to determine their initial condition. The experimental group was provided with visual media, while the control group was not given visual media. Data collection techniques included observation and short story writing test sheets. The assessment of short story writing skills focused on vocabulary, grammar, cohesion, and writing mechanics. The collected data will be analyzed. The results of the study indicate that writing short stories in English using visual media in the 7th grade at MTs Tarbiatul Islamiah inspires students to write short stories and helps them develop and express their ideas more fluently and coherently.